Analysis of Maghfirah Verses in Tafsir al-Munir and their Relevance to Enhancing the Value of Optimism in Modern Life - Mubarok, Abdul Hakiym Al; Azizah, Alfiyatul (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to analyze the construction of the meaning of maghfirah in Wahbah az-Zuḥailī’s Tafsīr al-Munīr and examine its relevance in building values of optimism in the context of modern life. The study positions maghfirah as a theological, semantic, ethical, and psychospiritual concept with significant implications for the moral development and inner well-being of individuals. Methodology: The research employs a qualitative design with content analysis of az-Zuḥailī’s interpretation of seven maghfirah-themed verses, reinforced by literature related to Qur’anic theology, ethics, and psychology. Data analysis is conducted through data reduction, narrative presentation, and structured conclusion drawing. Results: The findings indicate that az-Zuḥailī interprets maghfirah as a form of divine compassion and protection that is transformative, encompassing the purification of the soul, moral strengthening, and the opening of opportunities for life change. Each verse highlights specific emphases, ranging from universal forgiveness, divine love, to the restoration of spiritual rank, with consistency in the idea that maghfirah fosters hope and positive motivation. Applications/Originality/Value: This research contributes theoretically by mapping the role of maghfirah as the foundation of optimism within the psychospiritual framework of Islam and offers a model of understanding that can be applied in the development of Qur’anic ethics literature and studies in mental health based on religious values.